Diagnosis and treatment of osteoporosis following hip fracture in Chiang Mai University Hospital - Rojanasthien S. (2014)
Osteoporosis is defined as a skeletal disorder characterized by compromised bone strength predisposing a person to an increased risk of fracture. Hip fracture is the common and serious consequence of osteoporosis. To improve bone quality and prevent new fracture, osteoporosis should be treated while the patient was admitted with hip fracture problem. Several medications have been proven to be effective. Objectives of the present study were to determine the adequacy of diagnosis and treatment of osteoporosis in hip fracture patients.